Innovation of Islamic Elementary School in Strengthening Religious Character: Adaptive Strategy in the Digital Era - Cahyanto, Bagus; Nur Atiqoh Bela Dina, Lia; Nur Cholifah, Tety; Arif, Muhamad; Farahdilla, Ariska (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
This study aims to explore the innovations carried out by Sekolah Rendah Islam Al-Maarif Sungai Petani Malaysia in strengthening students' religious character. This study uses a qualitative case study approach with data collection techniques using interviews, observations, and documentation studies. The informants involved include the principal, teachers, students, and researchers using Miles, Huberman, and Saldana's qualitative data analysis. The results of the study indicate that the innovations carried out by the school in strengthening students' religious character are (a) internalization of character through intracurricular learning, (b) routine worship activities such as dhuha prayer, reciting the Koran, and dzuhur prayer in congregation, (c) the Tarbawi Champfire program, and (d) student organizations in the school. The results of this study provide insight into the innovations that have been carried out in strengthening students' religious character while opening up opportunities for further research including long-term evaluations of the effectiveness of the program in shaping students' religious character. These findings can then be adopted by other schools both in Malaysia and in other countries that have the same typology of Islamic education systems.